Antibiotic susceptibility pattern of Portuguese environmental Legionella isolates - Cruz, Carolina; Rodrigues, Lúcia; Fernandes, Filipa; Santos, Ricardo; Paixão, Paulo; Chasqueira, Maria Jesus (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Legionnaires’ Disease is a pneumonia caused by Legionella spp., currently treated empirically with fluoroquinolones and macrolides. In this study, we aim to describe the antibiotic susceptibility pattern of environmental Legionella recovered in the south of Portugal. Methods Minimal inhibitory concentration (MIC) determination of 57 Legionella isolates (10 Lp sg 1, 32, Lp sg 2-14 15 L. spp) was achieved by broth microdilution, as described by EUCAST, for azithromycin, clarithromycin, ciprofloxacin, levofloxacin, and doxycycline. Results Fluoroquinolones were the most active antibiotic, displaying the lowest MIC values in contrast to doxycycline which had the highest. MIC90 and epidemiological cut-off (ECOFF) values were, respectively, 0.5/1 mg/L for azithromycin, 0.125/0.25 mg/L for clarithromycin, 0.064/0.125 mg/L for ciprofloxacin, 0.125/0.125 mg/L for levofloxacin and 16/32 mg/L for doxycycline. Discussion MIC distributions were higher than reported by EUCAST for all antibiotics. Interestingly, two phenotypically resistant isolates with high-level quinolone resistance were identified. This is the first time that MIC distributions, lpeAB and tet56 genes have been investigated in Portuguese environmental isolates of Legionella.